Students' Perceptions of their Rights in Portugal - Veiga, Feliciano Henriques (2011)
The present study analyses young Portuguese students’perceptions of their rights at school and at home. The sample consisted of 294 male and female students, in Year 7 to Year 9, from several regions in the country. The assessment instrument used was the ‘Children’s Rights Scale’ (Hart, 1993; Hart et al., 1996) and results were related to a number of other questions regarding the following independent variables: (1) school variables (school year, school achievement, teacher’s support, violence at school); (2) family variables (parental authority, family cohesion, parents’ education); (3) personal variables (age, gender, professional interests). Significant relations were found between the students’ perceptions of their rights and these independent variables. In general, Portuguese students declare that their rights exist and are very important. Students who have a greater degree of personal limitations, or who live in worse school or family contexts, are the ones who indicate less importance and perceive less existence of rights at school and at home. The study gives directions to efforts to strengthen projects for the promotion of students’ rights by including training programs for teachers and parents, in a close net connection among school, family and significant social agents.